The radicalization of Abu Hamdie : wider lessons for the ongoing struggle against violent extremism in post-Marawi Mindanao - Kumar Ramakrishna (2020)
This essay examines the radicalization into violent extremism of a former Abu Sayyaf Group (ASG) militant named Abu Hamdie. It first explores the violent Islamist ASG milieu within which he found himself embedded. Second, it examines how his experiences within a strategic node of the violent Islamist ecosystem in Marawi, the Darul Imam Shafii religious boarding school, facilitated his own radicalization. The essay finally suggests three broad lessons that may be learned from the specific Abu Hamdie radicalization experience for the ongoing struggle against violent extremism in post-Marawi Mindanao: first, the ideological ecosystem of Islamist extremism of which Darul Imam Shafii was an important node must be dismantled; second, the role of long-standing Bangsamoro socio-political and historical grievances must be urgently addressed by the Philippine authorities and third, the increasingly pervasive influence of puritanical Wahhabi ideas, that have rendered impressionable young people susceptible to violent extremist ideological narratives, needs countering.